Institutional providing for financial crime investigation and fighting against terrorism financing in the context of economic security strengthening of the state. Lithuanian experience - Muravska (Yakubivska), Yulia (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article is devoted to the study of Lithuania’s experience in the context of institutional support for financial crimes investigation and combating the terrorism financing. Institutions responsible for financial investigations that have been actively forming in recent years in the European Union countries are oriented towards providing the highest level of protection and strengthening the country’s economic security. Lithuania actively strengthens its position in the context of institutional support for financial crimes investigation and combating the terrorism financing. The article analyzes the legal and regulatory framework for financial crime investigating and combating the terrorism financing in Lithuania and the EU. The conclusions about the current state and level of effectiveness of the institutional support system for financial crimes investigation and combating the financing of terrorism of the Republic of Lithuania are formulated